UPAYA SATRESKRIM DALAM MELAKUKAN PENYELIDIKAN GUNA MENINGKATKAN PENGUNGKAPAN TINDAK PIDANA CURAT DI WILAYAH HUKUM POLRES BREBES - M FAHMI SANUSI (Indonesian Journal of Police Studies, 2022)
ABSTRACT EFFORT OF INVESTIGATION BY SATRESKRIM TO IMPROVE THE DISCLOSURE OF BURGLARY CRIMES IN BREBES POLICE M FAHMI SANUSI Fahmisanusi1106@gmail.com Theft has now become a complex problem that is currently faced by the world including the Indonesian nation. It has been the main task of the police as law enforcement cracks down firmly on suspected perpetrators of theft crimes. However, in the investigation activities, there are weaknesses that make it not optimal, which is found to be factors - both internal factors such as human resources, infrastructure, supervision and external such as public behavior that hinders the investigation of burglary crimes. The preparation of this final project uses a qualitative approach with a type of field research. Then to discuss the problems of the investigation of theft crimes by Satreskrim Brebes researchers use SWOT theory, management and related concepts focus the problem in this final project. The factual conditions that the author encountered when carrying out the research were the weakness of the human resource element, namely the lack of investigative skills possessed by the personnel, which was indicated by the lack of personnel who attended vocational education and the lack of facilities and infrastructure. The problem solving step that the writer recommends is the optimization of human resources and infrastructure using SWOT theory, management and concepts related to the focus of the problem in this final project. . The results of this study can be concluded that the implementation of the investigation of burglary crimes in Brebes police has not been running optimally. This is indicated by the decrease in the number of disclosure of burglary crimes in the last 2 (two) year with several factors that affect it, among others, human resources that are not qualified and adequate, infrastructure that does not meet the needs of investigations, budgets that are not in accordance with the needs in the field, and supervision that has not been maximizedwhere this will be an obstacle in the investigation of theft crimes in Brebes police in the future. Keywords: Effort, Investigation, Satreskrim,burglary